1998
DOI: 10.1097/00006123-199811000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Outcomes, with Treatment Data, for Patients with Cerebral Aneurysms Treated with Guglielmi Detachable Coils: A Single-Center Experience

Abstract: This study details long-term clinical outcomes after GDC treatment and describes factors affecting the need for retreatment. Although complete anatomic cure was not obtained in all cases and the long-term protection from subarachnoid hemorrhage remains to be determined, these data indicate that GDC are a safe and efficacious treatment for cerebral aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
90
0
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 9 publications
13
90
0
6
Order By: Relevance
“…9,10 The Cerebral Aneurysm Re-rupture After Treatment (CARAT) study found a rate of rupture after treatment to be 1.8%, which is comparable to the 1.7% rerupture rate reported earlier in the International Subarachnoid Aneurysm Treatment study. 11 Recently, their subtotal occlusion cohort study of 1,010 patients treated with coil embolization or surgical clipping found that degree of occlusion was associated with a lower risk of rerupture.…”
Section: Comparison Of Endovascular Occlusion and Microsurgical Exclumentioning
confidence: 53%
See 2 more Smart Citations
“…9,10 The Cerebral Aneurysm Re-rupture After Treatment (CARAT) study found a rate of rupture after treatment to be 1.8%, which is comparable to the 1.7% rerupture rate reported earlier in the International Subarachnoid Aneurysm Treatment study. 11 Recently, their subtotal occlusion cohort study of 1,010 patients treated with coil embolization or surgical clipping found that degree of occlusion was associated with a lower risk of rerupture.…”
Section: Comparison Of Endovascular Occlusion and Microsurgical Exclumentioning
confidence: 53%
“…In the report by Kuether et al on 74 patients with 77 aneurysms, including both ruptured and unruptured aneurysms, the authors had no reported hemorrhage over a follow-up period of 1.9 years in those aneurysms that demonstrated complete exclusion. 9 In those with near-complete occlusion, a hemorrhage rate of 1.4% per year was found in the same follow-up period. 9 In a meta-analyses on the treatment of UIAs in 1,379 patients, Lanterna et al found a total of 13 nonprocedural bleeding events occurring in 703 eligible patients during an average follow-up time of 0.5 to 3.8 years.…”
Section: Comparison Of Endovascular Occlusion and Microsurgical Exclumentioning
confidence: 71%
See 1 more Smart Citation
“…Although the general usefulness of this method has been recognized and it is increasingly being considered an alternative to surgical clipping in selected patients (Pierot et al 1996;Pierot et al 1997;Eskridge and Song 1998;Kuether et al 1998;Lempert et al 2000)., the utility, efficacy, and safety in distinct patient populations are still in the process of being defined Guglielmi et al 1992;Bavinzski et al 1999;Brilstra et al 1999;Byrne et al 1999;Lempert et al 2000).…”
Section: Aneurysms Of the Posterior Circulationmentioning
confidence: 99%
“…Even after the development of innovative approaches to the skull base and technical improvements (Day et al 1997;Lawton et al 1997;Aziz et al 1999) the morbidity and mortality rates associated with their exposure remain high (Drake 1979;Hernesniemi et al 1992;Hillman et al 1996). Endovascular occlusion of intracranial aneurysms using Guglielmi electrolytically detachable coils (GDCs) has been accepted as a valuable therapeutic alternative to surgical clipping of basilar tip aneurysms in patients who were not candidates for surgical intervention because of their presentation in poor condition, advanced age or the difficult nature of their lesion (Guglielmi et al 1992;Peerless et al 1994;Bavinzski et al 1995;Nichols et al 1997;Kuether et al 1998;Bavinzski et al 1999;Byrne et al 1999). Basilar tip aneurysms in particular are well suited for endovascular approaches as for the distinct angiographic features of most of them.…”
Section: Basilar Apex Aneurysmsmentioning
confidence: 99%